MICROWAVE HOLOGRAPHIC SYSTEM WITH RING APERTURE FOR DETECTING PEOPLE BEHIND OPTICALLY OPAQUE OBSTACLES - P. D. Kuharchik; V. G. Semenchik; V. A. Pahomov (Приборы и методы измерений)
Microwave imaging system with ring aperture is considered. Image reconstruction algorithm is described; scattering function calculation and system resolution analysis are presented. Modeling process results of people detection behind optically opaque obstacles made by holographic system with ring aperture are presented.